AI READINESS AND MATURITY ASSESSMENT FOR ETHICAL AND RESPONSIBLE AI ADOPTION: A CASE STUDY OF PT SARANA MULTI INFRASTRUKTUR - Winny Claudia Anggreacia; Achmad Ghazali (RADJA PUBLIKA, 2026)
This study assesses the readiness and maturity level of PT Sarana Multi Infrastruktur (SMI), a state-owned development finance institution in Indonesia, for ethical and responsible artificial intelligence (AI) adoption. Employing a mixed-methods approach, the research integrates the Technology-Organization-Environment (TOE) framework, Technology Readiness Index (TRI), and IBM AI Adoption Maturity Model to evaluate AI readiness across multiple dimensions. Data were collected through questionnaires distributed to 84 employees with minimum five years of tenure and semi-structured interviews with five key stakeholders representing IT, Risk Management, Human Capital, Compliance & Legal divisions, and executive management. Results reveal high individual psychological readiness (TRI score: 3.61, Explorers classification) with strong optimism and innovativeness, yet critical institutional gaps in governance frameworks, data infrastructure, security protocols, and regulatory compliance mechanisms. PT SMI is classified at Phase 1, Initial Experiments of the IBM maturity model. Strategic recommendations include establishing comprehensive AI governance frameworks aligned with Indonesian regulations (PDP Law, SE Kominfo No. 9/2023, OJK AI Ethics), strengthening data and security foundations, and building employee risk awareness. This research provides actionable roadmap for responsible AI adoption in public sector financial institutions navigating digital transformation amid regulatory constraints.